PROFILE OF STUDENTS ANALYTICAL THINKING SKILLS IN LEARNING STYLE FOR COMPLETING SUBSTANCE PRESSURE PROBLEMS - Wirawan Fadly (Jambura Physics Journal, 2021)
The skill to think analytically is an important skill for students to have, where the skill to think analytically helps students solve problems in science lessons that require an analytical skill to solve them. The research method is qualitative with a naturalistic design. This research was conducted at some Junior High schools in Ponorogo using the purposive sampling technique. Data were collected using in-depth interviews, observation, and documentation, then analyzed using quantitative descriptive and qualitative descriptive. This study aims to determine the profile of students' analytical thinking skills in solving problem-based problems in the grade 8th at pressure material and determine the pattern of its relationship with scientific exploration. The results showed that: 1) the profile of the analytical thinking skill in terms of the learning styles of students, namely the visual style subjects intend to explain what is known through the direct explanation in more detail, the audiovisual subjects are more likely to form simpler patterns with reasoning patterns generalization and on kinesthetic subjects tend to apply different (unique) concepts, but still have a relationship with the problem, 2) the pattern of the relationship between analytical thinking skills and learning styles, namely the exploration of science, which includes aspects of experience, reasoning, modalities, and the mindset of students. Through the results of this study, it is hoped that it can provide theoretical and practical insights for educators in determining approaches and strategies for achieving science analytical competence according to students' learning styles at school.